Strategi Kepala Madrasah dalam Pengelolaan Kinerja Guru di MI Fatimah Sriwijaya Palembang - Saipul Annur; Baim, Ibrahim; Sintia Antira (Indo-MathEdu Intellectuals Journal, 2024)
This research is entitled "The Headmaster's Strategies in Managing Teacher Performance at MI Fatimah Sriwijaya Palembang." The research method used in this study is qualitative method with a qualitative descriptive approach. Data collection techniques include interviews, observations, and documentation. The research informants are the headmaster, teachers, and administrative staff. The technique used in qualitative data analysis consists of data reduction, data presentation, and subsequently drawing conclusions/verification. Triangulation in this study involves using source triangulation, technique triangulation, and time triangulation. The results of this study show that the strategy of the head of the madrasah in managing teacher performance is certainly implemented quite well through several indicators, namely rational empiritical strategy (by holding teacher council meetings), normal reducative strategy (dividing tasks according to teacher positions and areas of interest), fellowship strategy (social interaction between teachers in madrasahs), academic strategy (holding trainings, seminars, bimtek),  and engineering strategy (giving examples to all madrasah residents, especially teachers). Furthermore, the factors that influence the strategy of the head of the madrasah in managing teacher performance are good cooperation between colleagues, the existence of motivation that encourages morale, not only that in managing teacher performance limited funds are inhibiting factors, especially limited funds in facilities and infrastructure